Indonesian Cultural Perspective Critical Discourse Analysis in Junior High School Level English Textbooks - Muhammad Hafizh Agharid Adim; Mutiarani (Journal of English Language Learning, 2022)
Language is a tool for people to communicate with structured words and sentence patterns. However, when there is a language there is also a culture that bonds together with language. One of the language that the world use is English. English has a very high demand in every sectors including education sectors. In education sector, English serves as the main subject in EFL countries, one of the EFL countries is Indonesia, and the teaching and learning English activity in Indonesia is still relying on textbook. Textbooks in Indonesia is rarely showing a cultural content which cultural contents in the textbook can be one of the appreciation of preserving a traditional culture. In this research, the author will analyze the discourse that found in a Junior High School level textbook, English on Sky 2 whether there is any Indonesian Cultural Perspective that included within the textbook. This research method will be using a qualitative method with descriptive analysis as the approach of research design.